Air and Steam Gasification of Almond Biomass - McCaffrey, Zach; Thy, Peter; Long, Michael; Oliveira, Melina [UNESP]; Wang, Li; Torres, Lennard; Aktas, Turkan; Chiou, Bor-Sen; Orts, William; Jenkins, Bryan M. (Frontiers Media Sa, 2019)
Experiments were performed on a laboratory scale fluidized bed gasifier to characterize the gasification products of almond shell and hull removed in nut processing operations and to determine the effect of gasifying media on bed agglomeration. The higher heating value of syngas during air gasification of almond biomass ranged from 4 to 6 MJ m(-3) while gas concentrations ranged from 14 to 18% H-2, 3-4% CH4, 43-50% N-2, 16-19% CO, and 16-17% CO2. For steam gasification, higher heating value was 10-12 MJ m(-3) and gas concentrations were 35-40% H-2, 5-7% CH4, 17-21% N-2, 18-21% CO, and 16-18% CO2. The high level of potassium in the almond shells led to strong corrosion and bed agglomeration due to flue gas transport of potassium compounds. These resulting pervasive kalsilite reactions were significantly worse under air gasification than under steam gasification. As a result of prolonged duration and elevated temperature approaching 1,000 degrees C, the corrosinal reaction changes to formation of an adhesive potassium distillate melt locally forming strong bonds. This latter is interpreted as a result of aerosol transported of melt particles.
Keywords: almond biomass; air gasification; steam gasification; power generation; agglomeration